In Vitro Digestion and Fermentation of Cowpea Pod Extracts and Proteins Loaded in Ca(II)-Alginate Hydrogels - Traffano Schiffo, Maria Victoria (2024)
Antioxidants derived from food by-products are known for their bioactive properties and impact on human health. However, the gastrointestinal behavior is often poor due to their degradation during digestion. The development of Ca(II)–alginate beads supplemented with biopolymers and enriched with cowpea (Vigna unguiculata) extract could represent a novel environmentally friendly technological solution to produce functional ingredients in the food industry. The present study evaluates the impact of in vitro digestion/fermentation by analyzing global antioxidant response (GAR), production of short-chain fatty acids (SCFAs) as a modulation of gut microbiota, and behavior of proton transverse relaxation times by low-field nuclear magnetic resonance (as an indicator of gelation state and characterization of microstructure). Results revealed that guar gum and cowpea protein preserved a high GAR of total phenolic compounds and antioxidant capacity by ABTS and FRAP methods after digestion/fermentation, promoting an adequate protection of the bioactives for their absorption. Alginate-based beads have great potential as prebiotics, with the guar gum-containing system contributing the most to SCFAs production. Finally, the overall higher mobility of protons observed in the intestinal phase agrees with structural changes that promote the release of phenolic compounds during this stage. Beads are excellent carriers of bioactive compounds (cowpea phenolic compounds and peptides) with potential capacities.